Climate Change Projections for Tanzania Based on High-Resolution Regional Climate Models From the Coordinated Regional Climate Downscaling Experiment (CORDEX)-Africa - Luhunga, Philbert Modest; Kijazi, Agnes L.; Chang'a, Ladislaus; Kondowe, Afredy; Ng'ongolo, Hashim; Mtongori, Habiba (Frontiers in Environmental Science, 2018)
The impacts of climate change are predicted to compromise social-economic developments in developing countries. Adaptation is the only option to reduce the impacts. However, before starting determining adaptation strategies, it is important to conduct scientific research to understand possible pathways of future climate change under different emission scenarios. This is essential for having scientific facts that would guide the formulation of effective adaptation strategies. In this study, climate change projections for Tanzania is carried out using outputs of high resolution Regional Climate Models (RCMs) from the Coordinated Regional Climate Downscaling Experiment program (CORDEX). Future (2011–2100) projections of daily rainfall, minimum and maximum temperatures under two Representative Concentration Pathways (RCPs): RCP 8.5 and RCP 4.5 are compared with baseline (1971–2000) simulations. The comparison is based on determining the departure of future climate during present (2011–2040), mid (2041–2070) and end (2071–2100) centuries from baseline (1971–2000) climate condition. Results reveal that there are likely to be an obvious increased minimum and maximum temperature trend over the entire country in three future periods (2011–2040), (2041–2070), and (2071–2100) under both emission scenarios RCP 8.5 and RCP 4.5. This is especially true for the western parts of the country, southwestern highlands and the eastern parts of Lake Nyasa where maximum temperatures are projected to be greater than 3.5°C and in the range of 2 to 2.4°C under RCP 8.5 and RCP 4.5 emission scenarios respectively. The western sides of the Lake Victoria basin and parts of Northeastern highlands are likely to feature increased minimum temperatures in the range of 4.5 to 4.8°C under RCP 8.5 emission scenario. The cold season: June-July-August-September (JJAS) is likely to become warmer than the warm season that starts from October and continue to April or May. During JJAS season, the country is likely to experience increased maximum temperature in the range of 1.7 to 2.4°C and 2 to 4°C in mid (2041–2070) and end (2070–2100) centuries respectively. Rainfall over parts of northeastern highlands and Coastal regions is projected to increase in the range of 0.5 to 1 mm/day and 0.25 to 0.5 mm/day under RCP 8.5 and RCP 4.5 emission scenarios respectively. However, the western regions, southwestern highlands and eastern side of Lake Nyasa are likely to experience decreased amount of rainfall in the range of 0.5 to 1mm/day under both RCP 8.5 and RCP 4.5 emission scenarios.